Fact and Moral Value - a Comment on Dr Hudson's Paper - Helm, Paul (Religious studies, 1969)
In the first part of his paper, Dr Hudson argues that the distinction between between facts and values is eroded because there are some factual statements (those of institutional fact') from which moral judgments do follow; and secondly he argues that there is a non-contingent connexion between beliefs about man and what it is intelligible to approve of or disapprove of morally. Both these conclusions are argued for tentatively and with reservation. In this comment I want to discuss three of the many issues Dr Hudson raises, and then to touch on a more general point which is at the source of my dissatisfaction with the drift of Dr Hudson's paper.